PENGUJIAN KARAKTERISTIK BATERAI LITHIUM-ION DENGAN METODE FUZZY DENGAN BEBAN BERVARIASI - Thofiq Puji Cahyono; Triwahju Hardianto; Bambang Sri Kaloko (Fakultas Teknik, Universitas Jember, 2020)
The use of lithium-ion batteries today is very popular among the electronics world. Lithium-ion batteries are commonly used in electric vehicles to store electric energy electric vehicles. Government will also make inroads on electric vehicles. The Indonesian government targets that by 2020 it will carry 13 million electric vehicles and by 2030 will reach 100 million. Electric vehicles have no emissions or exhaust gases like conventional vehicles now. Electric vehicles also do not cause environmental pollution because they do not have exhaust gases and do not cause very noisy noise. In the study using fuzzy method and without using fuzzy method and done comparison with simulation results on simulink matlab. The results of lithium-ion battery testing when using fuzzy control with constant current 1,11 ampere obtained a capacity of 2,6 Ah and experienced a battery temperature increase of 2,44 celsius.While testing without using controls with a 10 watt lamp load obtained a battery capacity of 2,07 Ah and a battery temperature increase of 2,71 celsius. And when compared to simulations on simulink matlab obtained a capacity of 2,7 Ah. Keywords — Lithium-ion Batteries, Fuzzy Inference System, constant current.